Demam Berdarah Dengue Yang Memperburuk Progresifitas Penyakit Ginjal Kronik - Rahmawati Rahmawati; Rosdina Permata Kasih (Jurnal Anestesi, 2023)
A 63 year old male patient came to the emergency room with complaints of weakness since 5 days of SMRS. Complaints are accompanied by nausea, vomiting, pain throughout the stomach, and liquid bowel movements. The patient also complained of low back pain that spread to both legs and made it difficult to walk. The patient also feels that he is urinating a little and seems to be stuck. Two weeks ago the patient had a fever accompanied by a cough. On physical examination, BP 90/60 mmHg, HR 111 x/minute, RR 20 x/minute, BMI 20.3 kg/m2, suprapubic area tenderness, right CVA tapping pain. Investigations Hb 11.73 g/dl, urea: 73 mg/dl, creatinine: 3.45 mg/dl, tubex: negative, dengue Ig M: negative, dengue Ig G: positive. Abdominal ultrasound examination revealed multiple nephrolithiasis dextra. On chest X-ray examination, there was an increased bronchovascular pattern, an air bronchogram (+) with an impression of bronchitis. The finding of multiple nephrolithiasis dextra indicates that the patient's kidney failure is chronic in nature, however, DHF that is not treated properly causes worsening of kidney function, giving rise to the condition of ACKD.